2019
DOI: 10.3389/fnins.2018.01045
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Model Radiomic Biomarkers Predict Development of Mild Cognitive Impairment Progression to Alzheimer’s Disease

Abstract: Predicting progression of mild cognitive impairment (MCI) to Alzheimer’s disease (AD) is clinically important. In this study, we propose a dual-model radiomic analysis with multivariate Cox proportional hazards regression models to investigate promising risk factors associated with MCI conversion to AD. T1 structural magnetic resonance imaging (MRI) and 18F-Fluorodeoxyglucose (FDG) positron emission tomography (PET) data, from the AD Neuroimaging Initiative database, were collected from 131 patients with MCI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 80 publications
2
59
0
2
Order By: Relevance
“…Recently, one study using a machine learning program to evaluate structural brain changes using MRI as predictors of conversion reported very high AUC, and another study using voxelbased FDGPET also reported very good re sults [19,21]. Best results are though reported from stud ies using various biomarkers in combination [24,25]. However, to design a study to examine the discriminant power of a combination of biomarkers and a cognitive test is difficult due to a circularity problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, one study using a machine learning program to evaluate structural brain changes using MRI as predictors of conversion reported very high AUC, and another study using voxelbased FDGPET also reported very good re sults [19,21]. Best results are though reported from stud ies using various biomarkers in combination [24,25]. However, to design a study to examine the discriminant power of a combination of biomarkers and a cognitive test is difficult due to a circularity problem.…”
Section: Discussionmentioning
confidence: 99%
“…The use of various MRI and PET methods and cerebrospinal fluid (CSF) examination, measuring concentrations of amyloidβ, phosphorylated and total tau proteins, as well as other proteins, including inflam matory markers, have shown to be helpful in predicting patients with MCI and SCD who will convert to demen tia, especially to AD [16][17][18][19][20][21][22]. A recent Cochrane review, however, does not support the use of βamyloid PET as biomarker for AD, but studies examining the combina tion of cognitive tests with CSF proteins, MRI, and FDGPET have shown excellent results in identifying people with MCI that would convert to dementia [23][24][25]. However, the use of biomarkers are time and per sonnel consuming, costly, and some of them are inva sive, and, consequently, not ideal for use in daily clinical practice, except in subspecialized settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, given its power in capturing the microstructural changes in tissues and its correlation with clinical endpoints (17) and age progression (18,19), the use of radiomics is expected to increase in neurodegenerative disorders (20). Presently, radiomics has been applied to the diagnosis of neurodegenerative diseases, including Alzheimer's disease (AD), amyotrophic lateral sclerosis, and Machado-Joseph disease with conventional MRI (21)(22)(23)(24)(25), which have similar pathological changes with PD, such as atrophy, abnormal proteins, or iron deposition in many brain regions. In a longitudinal study, radiomics successfully detected microstructural changes in invisible normal-appearing white matter on conventional T2 fluid-attenuated inversionrecovery (FLAIR) images (18).…”
Section: Introductionmentioning
confidence: 99%
“…Sowohl von Zhou et al [75] als auch von Spasov et al [76] wurde untersucht, ob mithilfe von Radiomics vorhergesagt werden kann, ob leichte kognitive Störungen sich zu Alzheimer entwickeln. Obwohl beide mit demselben Patientenkollektiv arbeiten, der Datenbank der Alzheimer's Disease Neuroimaging Initiative (http://adni.loni.usc.edu/), unterscheiden sie sich in der Auswahl des Kollektivs und den eingesetzten Methoden.…”
Section: Multiomicsunclassified
“…Obwohl beide mit demselben Patientenkollektiv arbeiten, der Datenbank der Alzheimer's Disease Neuroimaging Initiative (http://adni.loni.usc.edu/), unterscheiden sie sich in der Auswahl des Kollektivs und den eingesetzten Methoden. In Zhou et al [75] wurde ein klassischer Ansatz verfolgt, bei dem aus MRT und 18 F-FDG-PET-Daten eine Radiomics Signatur erstellt wurde. MRT und PET-Scans wurden dabei nicht separat betrachtet, sondern mittels Wavelet-Transformation fusioniert.…”
Section: Multiomicsunclassified